Income Distribution and Sociopolitical Instability as Determinants of Savings: A Cross-Sectional Model - Venieris, Yiannis P.; Gupta, Dipak K. (Journal of Political Economy, 1986)
The purpose of this cross-national study is twofold. First, it introduces income distribution and sociopolitical instability as arguments in the savings function. Second, it presents some empirical evidence in relation to their quantitative effects on savings. It is shown that sociopolitical instability has profound effects on the savings ratio. It is also shown that the bulk of savings is produced by the middle income class. As a result a redistribution of income at the expense of the upper income class yields a constant or an increased savings ratio developing on whether such a redistribution includes the lower income class or not.